2013
DOI: 10.1172/jci69746
|View full text |Cite
|
Sign up to set email alerts
|

Somitic disruption of GNAS in chick embryos mimics progressive osseous heteroplasia

Abstract: Progressive osseous heteroplasia (POH) is a rare developmental disorder of heterotopic ossification (HO)caused by heterozygous inactivating germline mutations in the paternal allele of the GNAS gene. Interestingly, POH lesions have a bewildering mosaic distribution. Using clinical, radiographic, and photographic documentation, we found that most of the 12 individuals studied had a lesional bias toward one side or the other, even showing exclusive sidedness. Most strikingly, all had a dermomyotomal distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 51 publications
(65 reference statements)
3
31
0
1
Order By: Relevance
“…In fact, diagnostic mutational spectrum of POH and other forms of GNASbased heterotopic ossification have been suggested (3,21). Given that clinical observation of patients with POH had lesions showing exclusive sided ness, Cairns et al hypothesized that somatic mutations in a progenitor cell of somatic origin may act on a back ground of germline haploinsufficiency to cause loss of heterozygosity at the GNAS locus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, diagnostic mutational spectrum of POH and other forms of GNASbased heterotopic ossification have been suggested (3,21). Given that clinical observation of patients with POH had lesions showing exclusive sided ness, Cairns et al hypothesized that somatic mutations in a progenitor cell of somatic origin may act on a back ground of germline haploinsufficiency to cause loss of heterozygosity at the GNAS locus.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive osseous heteroplasia (POH; Online Mendelian Inheritance in Man [OMIM] 166350) is a rare condition characterized by invasive heterotopic ossification (1)(2)(3). It typically begins with dermal ossification during infancy and extends to the subcutaneous and deep connective tissues during childhood, leading to severe ankylosis of affected joints and focal growth retardation (1,4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ossifications in patients with POH can be limited to or be much more prominent on one side of the body, which suggests that the mechanism of the disease encompasses a second mutational mosaic hit or variations in GNAS imprinting or G s α expression 84 . Brachydactyly.…”
Section: The Definition Of Pth Resistance Is As Followsmentioning
confidence: 99%
“…66 Despite the association of germline GNAS mutations with POH, the resulting heterotopic ossification occurs in a mosaic pattern, suggesting that an as yet unknown "second hit" in addition to the GNAS mutation may be necessary. 193 Heterotopic bone likely reflects mis-differentiation of mesenchymal stem cells. 194 Past studies had shown that reducing expression of Gαs in mesenchymal stem cells induces ectopic expression of Cbfa1/Runx2 195 and collagen I and osteopontin, 196 early markers of osteoblast formation.…”
Section: Albright Hereditary Osteodystrophymentioning
confidence: 99%